An Efficient Decision Making Process for Vehicles Operations in Underground Mining - Sepulveda-Salas, J; Vasquez-Perez, O (EDP Sciences, 2015)
Day by day, the LHD (load-haul-dump) vehicle operator addresses the routing problems at the production level of mine, whose solution impacts on the performance of all the production chain. Unfortunately, the operator s goal of minimizing the makespan of his workload is not necessarily optimal as one needs to take into account the coordination with next operation levels. In this paper, we stated the problem to determine the working path of LHD vehicle for minimizing the makespan subject to the coordination between the production level and next the operation level, so called the reduction level. We prove that the problem is NP-hard in the strong sense, propose an exact formulation by a mixed integer linear programming (MIP) model and generate an approximation algorithm. From a real implementation point of view, we developed a simple-to-execute decision-making process (DMP) for the LHD vehicle operator based on the generated approximation algorithm. Finally, we study DMP performance by a numerical analysis based on data from the Chilean underground copper mine, called El Teniente. The results show that the approximation ratio in practice is only 1.08. © EDP Sciences, ROADEF, SMAI 2014.